Technical and Socio-Economic Constraints to Duck Production in the Philippines: A Productivity Analysis - Chang, Hui-Shung (Christie); Villano, Renato (International Journal of Poultry Science, 2008)
Two hundred and five duck egg producers in four provinces of the Philippines, including Iloilo, Nueva Ecija, Pampanga and Quezon, were surveyed in 2003. They were asked about their socio-demographic and farm characteristics, their income sources and problems encountered in the production and marketing of duck eggs, as well as their access to capital and extension service and their awareness of participation in, farmers` organizations and government programs. The results showed that there was significant diversity in farm size, farm management practices performance in duck farming. We also found from the basic data that duck farmers in the Philippines generally lacked technical know-how and access to capital and extension services encountered serious problems in production and marketing of duck products. Results from the productivity analysis show that the mean technical efficiency is 0.62, with the majority of the technical efficiency estimates being between 0.61 and 0.90. The key factors affecting technical efficiency included both social-economic factors such as education, access to loans and being a member of farmers organization and technical factors such as farm size and management practices. One policy recommendation is that well-targeted extension on technical know-how for duck farming, rather than record keeping or marketing, can help remove production constraints and improve productivity. In addition, more consumer research is needed to understand future demand for duck products in anticipation of any significant increases in supply due to productivity improvement.